A New Cytotoxic Prenylated Chalcone from Desmodium renifolium - Yang, Juan-Xia; Liu, Gui-You; Lou, Jie; Wang, Huan; Li, Li-Mei; Hu, Qiu-Fen; Ye, Yan-Qing (Asian Journal of Chemistry, 2015)
A new prenylated chalcone, 2',5-dihydroxy-4,4'-dimethoxy-3-prenyl-chalcone (1), was isolated from whole Desmodium renifolium plants. Its structure was determined by spectroscopic methods including 1D and 2D NMR. Compound 1 was evaluated for its cytotoxicity using five tumor cell lines ((NB4, A549, SHSY5Y, PC3 and MCF7). It exhibited cytotoxicity against NB4 and MCF7 cell with IC50 values of 5.8 and 6.9 μM, respectively.